Policy evaluation of village fund through an agro-tourism village for sustainable local development - Christina Tityanda Putri; Bintoro Wardiyanto; Falih Suaedi (Masyarakat, Kebudayaan dan Politik, 2020)
Village fund as a tool for policy strategy that Indonesia constructed from the periphery. The purpose of the village fund is to improve the welfare and quality of life of village people, manifested by encouraging the development of independent and sustainable villages with social, economic, and environmental resilience. The amount of budget allocation is designed to build Indonesia from a small scale and drive the revival and passion for creativity and innovation in all elements of the village. Pujon Kidul Village is a village in Malang District that serves as a reference ‘building village’ in the development of an agro-tourism village. Using a qualitative approach to a descriptive method, this research was collected from the village head and the government of Pujon Kidul, as well as NGOs and purposive societies, totaling approximately 15 informants. The findings show the development of tourism village Pujon Kidul has successfully brought change for the local community, especially in the development of human resources using natural resources. Both synergize and complement each other without elements of exploitation and are managed by the village-owned enterprises or Badan Usaha Milik Desa (BUMDesa), which has the authority to include the village in the government’s policy of building from the suburbs (village) to create sustainable development-based localities. Village level policy is a new era of the form of an independent government and encourages the realization of community participation to accelerate the progress of the village and leave the old village mindset behind.